Profile of Gram-Negative Bacteria Extended Spectrum Beta Lactamase Esbl in The Caecum of Broiler Chickens - Indratama, I Nyoman Yudayana; Rosyunita, Rosyunita; Hasbi, Nurmi; Octora, Metta; Rizqullah, Rifqi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Antimicrobial Resistance (AMR) is a global problem that causes increased morbidity, mortality, and healthcare costs. AMR arises from the irrational use of antibiotics in medicine and agriculture. This study aims to determine the profile of Gram-negative ESBL bacteria living in the cecum of broiler chickens. This study is a descriptive exploratory study using 5 chicken cecum samples taken from the Pagesangan market in Mataram city. The obtained bacteria were calculated by placing them on Macconkey agar media to count bacterial colonies. The results of this study showed that 20.1% of bacteria in the chicken cecum could grow on Macconkey media mixed with cefotaxime. Meanwhile, on Macconkey media without cefotaxime, 79.9% were obtained. Based on macroscopic, microscopic, and biochemical characteristics, it was found that the gram-negative bacteria obtained were Escherichia coli. In sensitivity tests, it was found that the bacteria were resistant to tetracycline (100%) and ampicillin (100%), and 25% were resistant to chloramphenicol. The conclusion is that gram-negative bacteria found in the cecum of broiler chickens, such as Escherichia coli, are resistant to several antibiotics. These bacteria are resistant to cefotaxime (20.1%), chloramphenicol (25%), tetracycline (100%), and ampicillin (100%).